A cooperação transfronteiriça entre Brasil e França na Amazônia e a ponte sobre o Rio Oiapoque - Nascimento, Hugo Gabriel Lima (2015)
International relations between Brazil and France, with regard to the border region, have been outlined during the 1990s, having greater intensification in 1996, due to the signing of the framework agreement, which was attended by state representatives of the countries mentioned above. That agreement led to the emergence of several initiatives in the field of cross-border cooperation, such as the proposed construction of a binational bridge over the Oiapoqueriver, Amapá (Brazil), linking French Guiana (France). Thus, the present study aims to investigate the role represented by the binational bridge on a new dynamic setting of cross-border cooperation between Brazil and France". The bridge is situated on the Oiapoqueriver, in Amazonian border region, between the cities Oiapoque, Amapá, and Saint Georges de L'oyapock, French Guiana. In terms of research methodology, this bibliographic study, which was conducted survey of official documents (reports, agreements, presidential speeches, interviews, among others) from France and Brazil related to border area in focus. The relevance of this work lies in the fact that allow reflection on the Amazon, seen as strategic political and diplomatic relations between Brazil and France, on the South American scenario. The survey results indicate that the bridge, completed in 2011, has not yet opened, favored the emergence of new possibilities of interaction and physical union in the southern cone countries, which in turn can enable the consolidation of relations between both countries, bringing development to the border area.